"Żelazne motyle". Inna strona kobiecości według Oriany Fallaci = "Iron butterflies". The other side of femininity by Oriana Fallaci - Tichoniuk-Wawrowicz, Ewa (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Alterity means being misunderstood as an individual, different from a hegemonic dominance (of some class, race, religion, gender etc.). However, the problem of alienation and oppression is not limited to cultural and geographical peripherality. According to Emmanuel Levinas, the feminine represents otherness in its absolute sense.
Keywords: Fallaci, Oriana (1929-2006); reportaż włoski; kobiecość